Pengaruh Latihan Singgle Leg Stride Jump dan Quick Leaf Terhadap Peningkatan Power Otot Tungkai Atlet Bola Voli Kumbung tahun 2022 - Sukarman (Jurnal Ilmu Sosial dan Humaniora, 2022)
The results of field observations that the Kumbung volleyball athlete's condition of leg muscle power is still not optimal, where in the last match the physical and jumping of volleyball athletes decreased so we need to conduct an evaluation, the most basic technique is related to the athlete's physical problems, especially leg muscle power where the role of muscle power is This leg is very important in addition to doing a jump smash it is also used to block the opponent's attack from above the net. Single leg stride jump and quick leaf plyometric exercises are a form of exercise to improve the leg muscle power of volleyball players. The objectives to be achieved in this study were to find out the effect of single leg stride jump exercise on increasing the leg muscle power of the 2022 Kumbung volleyball athlete and to find out the effect of quick leaf exercise on the increase in leg muscle power of the 2022 Kumbung volleyball athlete. experimental research "Pretest-posttest Design". The sample in this study was the total number of kumbung volleyball players totaling 14 people. The instrument used is the Vertical Jump test. The data analysis technique used in this research is the paired t test or commonly called the dependent sample t test. The results of the study of the Single Leg stride jump exercise group, the t-count value of 10.43 with the t-table 1.943 with a significant level of 5%, the t-count is greater than the t-table (10.43 > 1.943), thus the hypothesis is null (Ho ) is rejected and the alternative hypothesis (Ha) is accepted, meaning the results are significant. The quick leaf exercise group has t-count value of 5.733 with t-table 1.943 with a significant level of 5%, then t-count is greater than t-table (5.733 > 1.943), thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) accepted, it means that the result is significant. Research conclusions (1) There is an effect of single leg stride jump exercise on leg muscle power in men's kumbung volleyball in 2022". (2) There is an effect of quick leaf exercise on the smash ability of the men's kumbung volleyball in 2022".